On-site biosignal amplification using a single high-spin conjugated polymer - Gao-Yang Ge; Jingcao Xu; Xinyue Wang; Wenxi Sun; Mo Yang; Zi Mei; Xin-Yu Deng; Peiyun Li; Xiran Pan; Jia-Tong Li; Xue-Qing Wang; Zhi Zhang; et al. (Nature Communications)
Abstract On-site or in-sensor biosignal transduction and amplification can offer several benefits such as improved signal quality, reduced redundant data transmission, and enhanced system integration. Ambipolar organic electrochemical transistors (OECTs) are promising for this purpose due to their high transconductance, low operating voltage, biocompatibility, and suitability for miniaturized amplifier design. However, limitations in material performance and stability have hindered their application in biosignal amplification. Here, we propose using high-spin, hydrophilic conjugated polymers and a computational screening approach to address this challenge. We designed a high-spin polymer, namely P(TII-2FT), which exhibits satisfactory, stable, and balanced ambipolar OECT performance. The figure-of-merits achieved by the P(TII-2FT) devices surpass those of the current leading materials by 5 to 20 times, resulting in remarkable voltage gains while maintaining a compact form factor. Based on this amplifier, we have successfully achieved on-site capture and amplification of various electrophysiological signals with greatly enhanced signal quality.